2007
DOI: 10.1080/07420520701648309
|View full text |Cite
|
Sign up to set email alerts
|

Chronopharmacokinetics of Imipenem in the Rat

Abstract: There are no studies indicating a possible modification of imipenem pharmacokinetics related to the hour (i.e., circadian time) of its administration. The aim of this study was to evaluate the influence of different times of intramuscular imipenem administration on its disposition in Wistar AF EOPS rats. Four groups of eight animals were given a single intramuscular injection of 140 mg/kg of imipenem either at 10:00, 16:00, 22:00, or 04:00 h. Blood samples were collected 0.5, 1, 2, 3, 4, 6, and 8 h after drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Previous studies have reported temporal variations in relevant pharmacokinetic parameters calculated after the administration of various antimicrobial medications, such as norfloxacin (Rebuelto et al, 2003a), ceftriaxone (Rebuelto et al, 2003b), cephalexin (Prados et al, 2007), gentamicin (Widerhon et al, 2005), ciprofloxacin (Sarveshwer Rao et al, 1997), ampicillin (White et al, 1995), ceftibuten (Pan et al, 2003), amikacin (Bleyzac et al, 2000), and imipenem (Boulamery et al, 2007). The results of the present study showed that C max , t max , MRT, λ, t1 2 λ , and AUC calculated after the 08:30 h administration did not differ significantly from those calculated after the 20:30 h administration.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have reported temporal variations in relevant pharmacokinetic parameters calculated after the administration of various antimicrobial medications, such as norfloxacin (Rebuelto et al, 2003a), ceftriaxone (Rebuelto et al, 2003b), cephalexin (Prados et al, 2007), gentamicin (Widerhon et al, 2005), ciprofloxacin (Sarveshwer Rao et al, 1997), ampicillin (White et al, 1995), ceftibuten (Pan et al, 2003), amikacin (Bleyzac et al, 2000), and imipenem (Boulamery et al, 2007). The results of the present study showed that C max , t max , MRT, λ, t1 2 λ , and AUC calculated after the 08:30 h administration did not differ significantly from those calculated after the 20:30 h administration.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it is not unexpected that several studies have demonstrated that biological rhythms may influence the pharmacological effects of a variety of medications in animal models (e.g., Dridi et al, 2008) and humans (Bruguerolle, 1998(Bruguerolle, , 2008Smolensky & Peppas, 2007), including antibacterial ones (Beauchamp & Labrecque, 2007;Boulamery et al, 2007;Bruguerolle, 1998;Levi & Schibler, 2007;Ohdo, 2007;Rebuelto, 2006). Chronopharmacology examines the influence of time-of-day on drug pharmacokinetics and pharmacodynamics.…”
Section: Introductionmentioning
confidence: 97%
“…), timing (in reference to the sleep-wake cycle), and dose/intensity of usual treatments. Research papers pertaining to chronopharmacology-administration time (relative to the sleep-wake, menstrual, or annual cycle) differences in the kinetics and effects of medications-are expected to state the rationale for the choice of the treatment clock times, menstrual days, and months or seasons explored (Boulamery et al, 2007;Bruguerolle, 2008;Hermida et al, 2007;Karakucuk et al, 2006;Smolensky et al, 2007;Yegnanarayan et al, 2006).…”
Section: Chronobiological Criteriamentioning
confidence: 99%
“…Chronomedicine is the study of the chronobiology of health and disease and the translation of applicable findings to clinical medicine (Portaluppi, 2007). In the past few years, in particular, a chronobiological approach has been extensively used in medical research, leading to a better understanding of the pathophysiological mechanisms and features of many medical conditions and public health problems (Burioka et al, 2008;Colognesi et al, 2007;Kawahara et al, 2008;Lee et al, 2008;Leibowitz et al, 2007;Leiza et al, 2007;Lin et al, 2008;Mbanu et al, 2007;Ohkura et al, 2007;Perez-Lloret et al, 2008;Sadick et al, 2007;Sallinen et al, 2008;Shah et al, 2007;Tsai et al, 2007) as well as greater insight of therapeutic issues (Boulamery et al, 2007;Bruguerolle, 2008;Coudert et al, 2008;Dispersyn et al, 2008;Dridi et al, 2008;Hermida, 2007;Hermida et al, 2007bHermida et al, , 2008Prados et al, 2007;Smolensky et al, 2007;Tsuruoka et al, 2008).…”
Section: Introductionmentioning
confidence: 99%